2023
DOI: 10.1161/circulationaha.122.061451
|View full text |Cite
|
Sign up to set email alerts
|

Multiancestry Genome-Wide Association Study of Aortic Stenosis Identifies Multiple Novel Loci in the Million Veteran Program

Abstract: BACKGROUND: Calcific aortic stenosis (CAS) is the most common valvular heart disease in older adults and has no effective preventive therapies. Genome-wide association studies (GWAS) can identify genes influencing disease and may help prioritize therapeutic targets for CAS. METHODS: We performed a GWAS and gene association study of 14 451 patients with CAS and 398 544 controls in the Million Veteran Program. Replication was performed in the Million Vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…This was corroborated by evidence from the from the Emerging Risk Factors Collaboration [8], and in a large study on genetic variation in the LPA gene [7]. Following this, an association of high lipoprotein(a) with aortic valve stenosis was also identified [11,14], though whether high lipoprotein(a) levels contribute to aortic valve stenosis progression is less clear [15 & ]. High plasma lipoprotein(a) is also associated with risk of ischemic stroke, peripheral arterial disease, heart failure, cardiovascular mortality, and all-cause mortality [3…”
Section: Lipoprotein(a) As a Risk Factor For Cardiovascular And Nonca...mentioning
confidence: 80%
“…This was corroborated by evidence from the from the Emerging Risk Factors Collaboration [8], and in a large study on genetic variation in the LPA gene [7]. Following this, an association of high lipoprotein(a) with aortic valve stenosis was also identified [11,14], though whether high lipoprotein(a) levels contribute to aortic valve stenosis progression is less clear [15 & ]. High plasma lipoprotein(a) is also associated with risk of ischemic stroke, peripheral arterial disease, heart failure, cardiovascular mortality, and all-cause mortality [3…”
Section: Lipoprotein(a) As a Risk Factor For Cardiovascular And Nonca...mentioning
confidence: 80%
“…After the inception of calcification, the decreased compliance of the cusps leads to further mechanical stress, inducing a cycle whereby “calcium begets calcium” [14 ▪▪ ]. Permissive risk factors for CAVD include age, male sex, hypertension, smoking, obesity, congenital bicuspid morphology, genetic variants, LDL-cholesterol, Lp(a) and other apoB-containing lipoproteins [13,15 ▪▪ ,16 ▪▪ ,17 ▪ ].…”
Section: Reviewmentioning
confidence: 99%
“…Recent studies of association between Lp(a) and CAVD/AS are shown in Table 1[15 ▪▪ ,16 ▪▪ ,29 ▪▪ ,30 ▪▪ –36 ▪▪ ]. Many prior studies have reported Lp(a) concentration in mg/dl.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A multiancestry genome-wide association study in the million veteran programs recently showed that Lp(a) and LDL were both associated with calcific aortic stenosis, but the association of LDL was attenuated when adjusting for Lp(a) [51].…”
Section: Burning Questions To Be Addressedmentioning
confidence: 99%